Critical analysis of educational inclusion in a megadiverse social environment. Literature Review - Briones Morales , Víctor; Olvera Vera, Luis (Scripta Mundi, 2024)
The report focuses on inclusive education as a pedagogical approach that guarantees quality education, regardless of its differences, addressing educational environments; supported by legal regulations based on the principles of equity and inclusion, seeking to homogenize education. The objective is: Carry out a critical analysis of the problems faced by educational inclusion in a megadiverse environment. At the international level, the Universal Declaration of Human Rights and the Convention on the Rights of Persons with Disabilities highlight the importance of inclusive educational systems, in the context of megadiverse countries there are additional challenges. Methodologically, this work is based on the positivist paradigm, basic type, non-experimental design, bibliographic-documentary nature of relevant articles indexed in academic sources. It is identified that effective communication, inside and outside educational institutions. Additionally, adequate teacher training and collaboration between school, families, and the community are essential for the effective implementation of these policies. It is concluded that, to build a more just and equitable society, a joint effort is necessary to develop and strengthen inclusive educational strategies, adapting them to the diversity and needs of all students.